In situ observation of wave-induced deformation of submarine landslides in tidal channel areas - Xue, Liang; Liu, Hanlu; Li, Zhenghui; Sun, Zhongqiang; Shan, Hongxian; Jia, Yonggang (Frontiers in Earth Science, 2023)
Landslides often occur in land slopes, estuaries, fjords and intertidal zones in the marine environment, while the landslides in tidal channels has not been systematically reported. Zhoushan sea area is dotted with islands and crisscross tidal channels, which is a typical tidal channel development area. The data of coastal zone and island survey, offshore engineering site selection and environmental survey show that landslides are very common in tidal channel areas. The detailed study of this kind of landslide will enrich the research theory of submarine landslide, and have important guiding significance for marine planning, development and site selection and construction of coastal engineering in coastal areas. Firstly, the submarine landslide in the southwest of Zhujiajian island in Zhoushan is investigated in this paper. It is found that the sliding zone is parallel to the island coastline, with a length of about 250m and an extension of 2km, and the buried depth of the sliding surface is generally 8-10m; Then, through the self-developed seabed deformation observation system, combined with the hydrodynamic observation system, the landslide was observed in situ for 75 days. The observation results showed that the landslide creeps at a constant speed along the sliding surface under the action of weight, and the creep accelerates under the action of waves, multiple sliding surfaces are generated in the landslide body at the same time. Finally, the genetic mechanism of submarine landslide in tidal channel area is put forward.